#TITLE_ALTERNATIVE# - DELLIANSYAH (NIM: 12304034), RENDY
Crosshole seimic tomography arrival travel time is one of geophysics method that able to detect anomaly velocity in subsurface. Application of this method based on variation of travel time seimic wave propagation from source to receiver. Application of this method is simple because it only require first arrival travel from source and receiver and the data process is not to long. Study about tomography in this research using REFLEXW 4.5 software. Reconstruction study use a pile model in orders to testing the ability of the software for create an image tomography 2D with crosshole tomography method in the borehole. The testing are using two geometry aquisiton such as type-A and type-B. From the result, tomogram image from testing geometry acquisition type-B shown a good result. Its shown a pile shape from the anomaly velocity. While the geometry type-A only shown an anomaly velocity and do not shaped likes a pile. The research using the data real is located at seinsfled, District Kohlenz, Germany. Dominated sandstone are shown in this area with NE-SW trend of sedimentation deposition. The investigation of this research using crosshole seismic tomography method is to determine the area that have an anomaly of low velocity zone manifestation of the joint in the subsurface. Length of borehole separation is 48,25 meter and depth of borehole approximately 60 meter. Seismic source range and receiver in this research carried out to the test is P-Wave Sparker Probe SBS 36 and hydrophone chain. Interval of source and receiver is one meter. Both, source and receive, placed at depth 25,54 meter and 36 meter from the surface with total of 35 shot.The result from reconstruction shown a dominant anomaly low velocity zone is image between 44-45 meter. This anomaly resemble a circle shape with seismic velocity range from 2700-2800 m/s.